Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0194668
|View full text |Cite|
|
Sign up to set email alerts
|

Copy number of pancreatic polypeptide receptor gene NPY4R correlates with body mass index and waist circumference

Abstract: Multiple genetic studies have linked copy number variation (CNV) in different genes to body mass index (BMI) and obesity. A CNV on chromosome 10q11.22 has been associated with body weight. This CNV region spans NPY4R, the gene encoding the pancreatic polypeptide receptor Y4, which has been described as a satiety-stimulating receptor. We have investigated CNV of the NPY4R gene and analysed its relationship to BMI, waist circumference and self-reported dietary intake from 558 individuals (216 men and 342 women) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…GPRIN2 is a regulator of neurite outgrowth(45) and expressed in the hypothalamus(27; 46). PPYR1 encodes a receptor for neuropeptide Y (NPY) and pancreatic polypeptide (PP) a potential regulator of food intake(32). This gene region has a number of segmental duplications with variable coverage across microarrays making definitive conclusions about this region difficult and CNVs across this region are not rare in the general population Our findings appear to be consistent with the SOS with greater overall prevalence of 10q11.2 duplications in EO vs O.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…GPRIN2 is a regulator of neurite outgrowth(45) and expressed in the hypothalamus(27; 46). PPYR1 encodes a receptor for neuropeptide Y (NPY) and pancreatic polypeptide (PP) a potential regulator of food intake(32). This gene region has a number of segmental duplications with variable coverage across microarrays making definitive conclusions about this region difficult and CNVs across this region are not rare in the general population Our findings appear to be consistent with the SOS with greater overall prevalence of 10q11.2 duplications in EO vs O.…”
supporting
confidence: 55%
“…Smaller CNVs (both deletions and duplications) in this region have been associated with obesity(29)(30)(31). Increased copy number of PPYR1 (NPY4R), a gene within this region, have been associated with increased BMI, especially in women(32).…”
mentioning
confidence: 99%
“…The GPCR5 CNV deletion frequency was 0.025 in the Mexican population, and was not associated with obesity, which is consistent with the previous findings in Chinese individuals. Finally, previous studies associating the NPY4R CNV with obesity risk have reported contradictory findings, as the CNV deletion allele has been associated both with higher and lower obesity risk [ 14 , 15 , 41 , 42 ]. Our findings are consistent with the report of Sun et al, who found no association of this CNV deletion with obesity in the Chinese population [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was designed to investigate the previously reported CNV for the NPY4R gene on chromosome 10q11.22 and study the range of the CNV. Earlier studies were contradictory with the majority of studies reporting CNV [2, 5, 711, 14] and one study describing no variation in this genomic region [12]. Here, we demonstrate that the NPY4R copy number varied depending on the analysis method and the quality of data.…”
Section: Discussionmentioning
confidence: 47%
“…Most of the previous reports assumed that the normal copy number of NPY4R is 2 copies per genome [5, 9, 1113] and describe the CNV as either gain or loss, not always specifying the exact copy number. Several studies have demonstrated that a CNV in this region is associated with differences in body weight [2, 5, 11, 13, 14].
Fig.
…”
Section: Introductionmentioning
confidence: 99%